2019
DOI: 10.1111/myc.13005
|View full text |Cite
|
Sign up to set email alerts
|

Role of major facilitator superfamily transporter Qdr2p in biofilm formation by Candida glabrata

Abstract: Summary Candida glabrata represents the second‐most frequent cause of candidiasis infections of the mucosa, bloodstream and genito‐urinary tract in immunocompromised individuals. The incidence of C glabrata infection has increased significantly in the last two decades, mainly due to this species’ abilities to resist various antifungal drugs and to form biofilms. We focused on the relationship between biofilm formation and the product of QDR2, a C glabrata member of the major facilitator superfamily (MFS) gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Four, Out of the 10, Drug:H + Antiporters in C. glabrata Are Required for Biofilm Development Given the previous implication of CgQdr2 and CgTpo1_2 in biofilm formation in C. glabrata Widiasih Widiyanto et al, 2019), a systematic analysis of the possible involvement of all DHA1 transporters in this pathogenic yeast was carried out. The ability of the KUE100 wild-type strain and derived deletion mutants cgaqr1, cgqdr2, cgtpo1_1, cgtpo1_2, cgtpo3, cgtpo4, cgflr1_1, cgflr1_2, cgyhk8, and cgdrt1 to form biofilms was assessed in SDB pH 5.6 and RPMI pH 4 media, on polystyrene, by the crystal-violet assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four, Out of the 10, Drug:H + Antiporters in C. glabrata Are Required for Biofilm Development Given the previous implication of CgQdr2 and CgTpo1_2 in biofilm formation in C. glabrata Widiasih Widiyanto et al, 2019), a systematic analysis of the possible involvement of all DHA1 transporters in this pathogenic yeast was carried out. The ability of the KUE100 wild-type strain and derived deletion mutants cgaqr1, cgqdr2, cgtpo1_1, cgtpo1_2, cgtpo3, cgtpo4, cgflr1_1, cgflr1_2, cgyhk8, and cgdrt1 to form biofilms was assessed in SDB pH 5.6 and RPMI pH 4 media, on polystyrene, by the crystal-violet assay.…”
Section: Resultsmentioning
confidence: 99%
“…CgDtr1 has a role in the survival upon phagocytosis, being necessary for the resistance to oxidative and acetic acid stress . More recently, CgQdr2 was also identified as playing a role in biofilm formation, although the underlying mechanisms remained elusive (Widiasih Widiyanto et al, 2019). All the roles described for MFS transporters highlight their promiscuity in transporting many different substrates, which appear to ultimately lead to unexpected roles in processes, such as virulence, immune system evasion, or biofilm formation.…”
Section: Introductionmentioning
confidence: 99%
“…C. glabrata biofilms were formed according to an in vitro method using a 96-well flat-bottom polystyrene plate (IWAKI, Japan) (Widiasih Widiyanto et al, 2019). Yeast cells were cultured overnight at 37 • C. Cells were harvested by centrifugation and washed twice in 100 µL sterile phosphate-buffered saline buffer (PBS, 137 mmol/L NaCl, 2.7 mmol/L KCl, 10 mmol/L Na 2 HPO 4 , 2 mmol/L KH 2 PO 4 , pH 7.2).…”
Section: Biofilm Formation and Plate Siliconizationmentioning
confidence: 99%
“…In addition to proteins that act on cell wall synthesis related to the adhesion step during biofilm formation, some recent studies have reported that the multidrug resistance transporters Pdr16p and Tpo1_2p contribute to azole resistance and are related to biofilm formation (Culakova et al, 2013;Santos et al, 2017). More recently, Dtr1p, Qdr2p, and Tpo4p drug:H + antiporters were found to be associated with biofilm formation of C. glabrata (Widiasih Widiyanto et al, 2019;Santos et al, 2020). Thus, it seems like a broad range of proteins, which are valuable to study, affect the process of biofilm formation of C. glabrata.…”
Section: Introductionmentioning
confidence: 99%